Clinicopathological characteristics and oncological outcomes in a case of primary ovarian adenosarcoma with sarcomatous differentiation: a case report and literature review - Fatima, Sheereen; Shaikh, Imran N.; Shaikh, Naseem I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mullerian adenosarcoma is a rare malignant tumor generally involving the uterine corpus but can uncommonly involve extrauterine organs. Ovarian adenosarcoma is extremely rare and often diagnosed in young women. Majority of them are low grade with a good prognosis except for adenosarcoma with sarcomatous overgrowth (SO). We report a case of a large sized ovarian adenosarcoma with SO with elevated levels Ca125 and Ca19.9 and having disease free interval of approximately 1.5 years.